2021
DOI: 10.1002/jcsm.12780
|View full text |Cite
|
Sign up to set email alerts
|

Glycine increases fat‐free mass in malnourished haemodialysis patients: a randomized double‐blind crossover trial

Abstract: Background Protein energy wasting is associated with negative outcome in patients under chronic haemodialysis (HD). Branched‐chain amino acids (BCAAs) may increase the muscle mass. This post hoc analysis of a controlled double‐blind randomized crossover study assessed the impact of BCAAs on nutritional status, physical function, and quality of life. Methods We included 36 chronic HD patient features of protein energy wasting as plasma albumin <38 g/L, and dietary intakes <30 kcal/kg/day and <1 g protein/kg/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The few results obtained in rodent models are detailed in the following paragraph. However, unexpectedly, glycine supplementation in chronic haemodialysis patients was found to improve fat-free mass index, compared to BCAA [13 ▪ ]. Although it is outside the scope of the present review, it is worth mentioning this work, but it remains to be demonstrated that long-term glycine supplementation improves clinical outcomes in chronic haemodialysis patients or may benefit other patients.…”
Section: Confirmation and New Breakthroughs Brought By The Latest Cli...mentioning
confidence: 82%
“…The few results obtained in rodent models are detailed in the following paragraph. However, unexpectedly, glycine supplementation in chronic haemodialysis patients was found to improve fat-free mass index, compared to BCAA [13 ▪ ]. Although it is outside the scope of the present review, it is worth mentioning this work, but it remains to be demonstrated that long-term glycine supplementation improves clinical outcomes in chronic haemodialysis patients or may benefit other patients.…”
Section: Confirmation and New Breakthroughs Brought By The Latest Cli...mentioning
confidence: 82%
“…No significant effect on upper and lower body strength was reported in resistance-trained adults with a single oral glycine bolus of 0.3 g/kg body weight 1 h prior to assessment [ 61 ]. Patients undergoing chronic haemodialysis with protein energy wasting (PEW) showed positive effects, including improvements in handgrip strength and fat-free mass index following oral glycine administration of 7 g X 2/day over 4 months [ 45 ] (Table 1 , Fig. 2 , Supplementary Table A ).…”
Section: Resultsmentioning
confidence: 99%
“…In diseased populations, positive effects included mitigation of symptoms in patients with overactive bladder administered with 3 g X 2/day of oral glycine over 4 weeks; and decreased daily proteinuria in early preeclampsia patients administered with placebo 1% glycine solution for up to 7 days [ 35 ]. Although increased levels of pre-dialysis urea and normalised protein catabolic rate (nPCR) were reported in chronic haemodialysis patients with PEW following oral glycine administration of 7 g X 2/day over 4 months, these results were attributed to the patients’ compliance to glycine treatment [ 45 ] (Table 1 , Fig. 2 , Supplementary Table A ).…”
Section: Resultsmentioning
confidence: 99%
“…Creatine and glycine supplements were also investigated in two separate pilot randomized controlled trials. The results of both were promising, though larger trials are needed before routine adoption of these supplements in recommended [65,66].…”
Section: Novel and Emerging Treatmentsmentioning
confidence: 97%